Breast cancer in a male patient with a BRCA1 mutation - a case report - Krajewski, Piotr; Krajewska, Agata; Żukowska, Magdalena (Journal of Education, Health and Sport, 2018)
A 71-year-old patient with BRCA 1 mutation and breast cancer diagnosed in prophylactic screening. This case shows how crucial prophylactic screening is. BRCA1-positive patients, both men and women, need to be under special care, hence the diagnostic process and treatment should take place in highly specialized centers.